Assessment of environmental plasticity and stability of naked oats samples by productivity (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
Due to its nutritional qualities, naked oats are a valuable crop. Under favorable growing conditions, modern naked oats varieties are able to give a consistently high yield. At the same time, the low adaptability of varieties in changing environmental conditions leads to a decrease in yield. Therefore, the main task of crop breeding is the creation of high-yielding varieties with a high adaptability potential. The main goal of the study was to evaluate 45 genotypes of naked oats in the conditions of the Left Bank Forest Steppe of Ukraine by productivity and indicators of ecological plasticity and stability. The task of the study was to select the best samples with a high degree of adaptability. For a comprehensive adaptability assessment, the ecological plasticity and stability of the samples were determined, calculating the linear regression (bi), ecological stability (σd²), index of environmental conditions (Ij). The conditional environmental index (Ij) in 2019 and 2021 was positive and equal to 1.0 and 3.5, respectively. In 2020, it had a negative indicator of Ij = -4.6 and was characterized as unfavorable for naked oats productivity. Aldan, Boudrais, Agramak, Bekas and Vyrovets samples had the highest productivity value. The calculations of linear regression (bi) made possible to determine that such samples as OM 11-3007/3, AC Percy, Boudrais, Vyatsky belong to the group of intensive type samples, whereas samples of Vandrounyk and Valdin 765  highly depend on growing conditions, and Treasure of Ukraine, Baguette, Aldan, Taidon and Tarsky Holozerny samples are more stable. According to the results of the ecological stability calculation (σd²), it was established that Treasure of Ukraine, OM 11-3007/3, Saul, Solomon, Rhianon, AC Percy, Percheron and Progress, Tyumensky Holozerny samples are the most stable (σd²=0.0) by the productivity level during the years of the study. As a result of the study, the most valuable samples such as Treasure of Ukraine (bi=0.9; σd²=0.0), Solomon (bi=0.8; σd²=0.0), Levsha (bi=0.6; σd²=0 ,1), Aldan (bi=0.9; σd²=0.1), Taidon (bi=0.9; σd²=0.1) and Tarskiy Holozerny (bi=0.9; σd²=0.5) were selected, they have high environmental plasticity and stability close to zero.
Keywords: naked oats; samples; productivity; adaptability; plasticity; stability